Penerapan Keselamatan Dan Kesehatan Kerja Rumah Sakit (K3RS) di Rumah Sakit Umum X Jakarta - Suprapto; Ahmad, Affan (MPI Press, 2021)
Introduction: Hospital as a health service institution for thecommunity is a workplace that has a high risk to the safety andhealth of hospital human resources, patients, patient companions,visitors, and hospital environment so that the hospital is obliged toimplement the Republic of Indonesia Ministerial Regulation No. 66of 2016 concerning Hospital Work Safety and Health Standards.Objectives: The purpose of this study was to determine theImplementation of Occupational Safety and Health Standards at theJagakarsa Regional Hospital in 2019.Method: This type of research is qualitative using 5 informants.Result: From the results of research Jagakarsa Hospital hasimplemented the application of occupational safety and healthstandards of the hospital which include risk management, safetyand security, occupational health services, Management ofhazardous and toxic materials (B3) from aspects of occupationalsafety and health, fire prevention and control, management hospitalinfrastructure from aspects of occupational safety and health,management of medical equipment from aspects of occupationalsafety and health, preparedness to deal with emergencies ordisasters have been implemented well by Jagakarsa RegionalHospital but in reality there are still some elements that have notbeen carried out according to the Occupational Safety and HealthStandards diseases including risk management, fire control andprevention as well as hospital infrastructure.Conclution: Jagakarsa Regional Hospital should complement theshortcomings in the field so that it can realize the dream of thehospital becoming a favorite and perfect hospital